The canonical DHHC motif is not absolutely required for the activity of the yeast S-acyltransferases Swf1 and Pfa4 - González Montoro, María Ayelén (2015)
Protein S-acyltransferases, also known as palmitoyltransferases (PATs), are characterized by the presence of a 50-amino acid domain called the DHHC domain. Within this domain, these four amino acids constitute a highly conserved motif. It has been proposed that the palmitoylation reaction occurs through a palmitoyl-PAT covalent intermediate that involves the conserved cysteine in the DHHC motif. Mutation of this cysteine results in lack of function for several PATs, and DHHA or DHHS mutants are used regularly as catalytically inactive controls. In a genetic screen to isolate loss-of-function mutations in the yeast PAT Swf1, we isolated an allele encoding a Swf1 DHHR mutant. Overexpression of this mutant is able to partially complement a swf1Δstrain and to acylate the Swf1 substrates Tlg1, Syn8, and Snc1. Overexpression of the palmitoyltransferase Pfa4DHHAorDHHRmutants also results in palmitoylation of its substrate Chs3. We also investigated the role of the first histidine of the DHHC motif. A Swf1 DQHC mutant is also partially active but a DQHR is not. Finally, we show that Swf1 substrates are differentially modified by both DHHR and DQHC Swf1 mutants. We propose that, in the absence of the canonical mechanism, alternative suboptimal mechanisms take place that are more dependent on the reactivity of the acceptor protein. These results also imply that caution must be exercised when proposing non-canonical roles for PATs on the basis of considering DHHC mutants as catalytically inactive and, more generally, contribute to an understanding of the mechanism of protein palmitoylation